2014
DOI: 10.1007/s11745-014-3916-5
|View full text |Cite
|
Sign up to set email alerts
|

The Synergism of Biochemical Components Controlling Lipid Oxidation in Lamb Muscle

Abstract: Lipid oxidation of M. longissimus lumborum in fresh or vacuum packaged (aged) lamb meat stored at 3 °C for 0 or 4 weeks, respectively and displayed under refrigerated conditions for a further 4 days was assessed by measuring the concentration of malondialdehyde (MDA) in meat using the thiobarbituric acid reactive substances procedure. The effects of vitamin E, heme iron and polyunsaturated fatty acids (n-6 and n-3) on lipid oxidation were examined. Results showed a strong positive relationship between heme iro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(41 citation statements)
references
References 38 publications
4
35
0
Order By: Relevance
“…This threshold concentration was 3.5-4.0mg/kg of vitamin E (figure 3), similar to those reported in beef, 3.0-3.3 mg -tocopherol/kg tissue (Arnold et al, 1993;Faustman et al, 1989), and in the range previously reported for lamb, 2.26-5.3 -tocopherol/kg tissue (Ponnampalam et al, 2014;Hopkins et al, 2013;Álvarez et al, 2008;Lopez Bote et al, 2001). By comparison the maximum concentration expected for muscle is probably 6-10 mg/kg (Wulf et al1995;Chan, Hakkarainen, Faustman, Schaefer, Scheller & Liu, 1996) so the threshold level for colour stability occurred at about half…”
Section: Colour Stabilitysupporting
confidence: 89%
See 2 more Smart Citations
“…This threshold concentration was 3.5-4.0mg/kg of vitamin E (figure 3), similar to those reported in beef, 3.0-3.3 mg -tocopherol/kg tissue (Arnold et al, 1993;Faustman et al, 1989), and in the range previously reported for lamb, 2.26-5.3 -tocopherol/kg tissue (Ponnampalam et al, 2014;Hopkins et al, 2013;Álvarez et al, 2008;Lopez Bote et al, 2001). By comparison the maximum concentration expected for muscle is probably 6-10 mg/kg (Wulf et al1995;Chan, Hakkarainen, Faustman, Schaefer, Scheller & Liu, 1996) so the threshold level for colour stability occurred at about half…”
Section: Colour Stabilitysupporting
confidence: 89%
“…However, lipid peroxidation during retail display will increases with ageing and thus aging leads to a decline in the colour stability of meat after the product has been cut for retail display (Ponnampalam, Norng, Burnett, Dunshea, Jacobs & Hopkins, 2014;Wulf et al, 1995). This is…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…A strong positive relationship between haem iron, n‐6 and n‐3 fatty acids and lipid oxidation, when vitamin E was below 2.95 mg kg −1 muscle, was reported previously by Ponnampalam et al . (). Polar ETE contained 208 mg g −1 phenolic compounds, its ORAC value was 936 TE g −1 .…”
Section: Resultsmentioning
confidence: 97%
“…This is low relative to the concentrations found in meat from grass fed bison (3.47 µg × g -1 ) and grain finished beef (2.20 µg × g -1 ; Galbraith et al, 2016). In lamb, concentrations of vitamin E in muscle below 3 µ × g -1 has resulted in a higher rates of lipid oxidation (Ponnampalam et al, 2014). Proximate analysis of the ground lean and fat used to manufacture burger patties had an average fat content of 114.6 ± 22.2 mg × g -1 (range: 70.2 to 169.5 mg × g -1 ).…”
Section: Fatty Acid and Proximate Composition Of Bison Loin And Burgersmentioning
confidence: 77%